2021
DOI: 10.1016/j.omtm.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analytical techniques to quantitate the capsid content of adeno-associated viral vectors

Abstract: Adeno-associated virus (AAV) vectors, which contain a DNA transgene packaged into a protein capsid, have shown tremendous therapeutic potential in recent years. An inherent characteristic of the manufacturing process is production of empty capsids that lack the transgene and are therefore unable to provide the intended therapeutic benefit. The effect of empty capsids on clinical outcomes is not well understood, but there are immunogenicity and efficacy concerns, and these empty capsids are considered a product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…While CDMS was not used to quantitate particle content for the mixtures in this study, the data included represent a proof of concept that the technology could be used for such purposes. A similar study was performed on AAV capsids, which demonstrated that CDMS was highly complementary to AUC ( Werle et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While CDMS was not used to quantitate particle content for the mixtures in this study, the data included represent a proof of concept that the technology could be used for such purposes. A similar study was performed on AAV capsids, which demonstrated that CDMS was highly complementary to AUC ( Werle et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
“…Capsid protein analysis via reversed-phase high performance liquid chromatography (RP-HPLC) can also parse out particle maturity via analysis of viral protein content and processing ( Lehmberg et al, 1999 ; Vellekamp et al, 2001 ; Chelius et al, 2002 ; Takahashi et al, 2006 ). In addition to the more routine techniques, additional-state-of-the-art techniques, including charge detection mass spectrometry (CDMS) ( Contino and Jarrold, 2013 ; Pierson et al, 2016 ; Draper et al, 2018 ; Draper and Jarrold, 2019 ) are available for direct mass determination of intact viral particles ( Kondylis et al, 2019 ; Werle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with capsids that have packaged the full genome of interest, empty capsids are generated, and some capsids package a partial genome. − The encapsidation of DNA impurities, such as heterogeneous fragments of host cellular, helper, or plasmid DNAs, also occurs. , Finally, aggregation can reduce bioavailability and influence biodistribution and may also cause an immune response . CDMS has emerged as a valuable tool to analyze the DNA content of rAAV vectors. , It can go beyond characterization of the empty/full ratios and provide information about particle heterogeneity including packaging of heterogeneous DNA Figure a shows a CDMS mass distribution measured for empty AAV8 particles separated by ultracentrifugation with a CsCl gradient.…”
Section: Applications Of Cdms To Molecular Biology and Biotechnologymentioning
confidence: 99%
“…225 CDMS has emerged as a valuable tool to analyze the DNA content of rAAV vectors. 222,226 It can go beyond characterization of the empty/full ratios and provide information about particle heterogeneity including packaging of heterogeneous DNA. 227 Figure 10a shows a CDMS mass distribution measured for empty AAV8 particles separated by ultracentrifugation with a CsCl gradient.…”
Section: Analysis Of Gene-therapy Vectorsmentioning
confidence: 99%
“…Table 1 provides an overview of methods commonly used for detecting full and empty capsid particles. A recent comparison of these techniques demonstrated good correlation between the listed methods [ 40 ]. Within this set of orthogonal methods, AUC is a popular technique due to its capability of discriminating the population of partially filled capsids, a population that is gaining more and more interest in the industry.…”
Section: Introductionmentioning
confidence: 99%